Understanding digital piracy through the lens of psychosocial, criminological and cultural factors. (2017) - Sahni, Sanjeev P.; Jain, Garima; Gupta, Indranath
World's leading reports on piracy published by organisation such as WIPO and BSA have not explicitly explained the act of digital piracy from a psychosocial, cultural and criminological perspective. A total of 624 studies were identified which discussed the digital piracy phenomenon from varied perspective such as economic, political, legal, cultural, psychological, criminological and sociological factors. Relevant papers were further shortlisted from the identified studies by following an inclusion criterion of psychosocial, criminological and cultural factors that impact the behaviour of the perpetrators of digital piracy. Based on these criteria, 74 studies were included in this review which included following factors: social learning theory, self-control theory, neutralising techniques and justification of perpetrators, ethical, moral and religious predisposition of digital piracy. Theoretical constructs in explaining digital piracy and collectivistic and individualistic economies. It also identified potential area of future research based on critical construct of existing literature.